Trends and Associated Risk Factors of Caesarean Deliveries in Northeast State of India - Haobijam, Sharatchandra; Elangbam, Inaobi (National Journal of Community Medicine, 2025)
Background: Caesarean (C-section) deliveries are rising across India, with National Family Health Survey (NFHS-4, 2015–16) reporting 17.2% of births by C-section. This study investigates the variations in C-section prevalence and the associated factors in the Northeastern states compared to the rest of the country. Methods: This study analyses data collected from 232920 mothers under NFHS-5 (2019-2021). Bivariate analysis followed by logistic regression model was used to determine the risk factors associated with the C-sections based on the different criteria. Results: In NFHS-4 and NFHS-5, Telangana reported the highest rates at 57.7% and 60.7%, respectively, and Nagaland reported the lowest at 5.7% and 5.2% respectively. C-section rates rise steadily up to age 39, then decline among mothers aged 40–49. C-section deliveries rise sharply among highly educated women, a trend consistent in both the Northeast and the rest of India. Mothers with high blood pressure, birth order of one, six or more antenatal visits, a past terminated pregnancy show higher rates of C-section in both Northeast and the rest of India. Conclusion: Medical risk factors like antenatal visits and birth order strongly predict C-sections. This study highlights the complex interplay of medical and socio-economic factors influencing C-section rates across different regions.